2017
DOI: 10.1080/10408398.2015.1072083
|View full text |Cite
|
Sign up to set email alerts
|

Biological activity of Stevia rebaudiana Bertoni and their relationship to health

Abstract: The leaves of Stevia rebaudiana Bertoni has nutrients and phytochemicals, which make it an adequate source for the extraction and production of functional food ingredients. Preclinical and clinical studies suggest therapeutic and pharmacological applications for stevia and their extracts because they are not toxic and exhibit several biological activities. This review presents the biological activity of Stevia rebaudiana Bertoni and their relationship to antidiabetic, anticariogenic, antioxidant, hypotensive, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
11

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 52 publications
1
57
0
11
Order By: Relevance
“…In agreement with these results, we demonstrated a significant reduction in the activities of SID, CAT and GPx in the present study, with a significant increase in lipid peroxidation marker (MDA). Also, many authors have reported the direct antioxidant activity of extracts from the leaves of Stevia rebaudiana Bertoni, owing to the presence of alkaloids, flavonoids, and polyphenols (Ruiz-Ruiz et al, 2017). In the present study, we demonstrated that Stevia extract, stevioside and chlorogenic acid caused a significant increase in the activities of SOD, CAT and Gpx, together with a significant reduction in lipid peroxidation (MDA) in soleus muscle.…”
Section: Discussionsupporting
confidence: 67%
“…In agreement with these results, we demonstrated a significant reduction in the activities of SID, CAT and GPx in the present study, with a significant increase in lipid peroxidation marker (MDA). Also, many authors have reported the direct antioxidant activity of extracts from the leaves of Stevia rebaudiana Bertoni, owing to the presence of alkaloids, flavonoids, and polyphenols (Ruiz-Ruiz et al, 2017). In the present study, we demonstrated that Stevia extract, stevioside and chlorogenic acid caused a significant increase in the activities of SOD, CAT and Gpx, together with a significant reduction in lipid peroxidation (MDA) in soleus muscle.…”
Section: Discussionsupporting
confidence: 67%
“…Los esteviósidos se han catalogado como agentes antioxidantes, antiinflamatorios, antihipertensivos y reguladores de niveles de glucosa en sangre (55,56). Las investigaciones en el 2015 afirmaban que el consumo de este edulcorante no presentaba ningún riesgo para la salud, aun en combinación con otros fármacos como la metformina (57).…”
Section: Edulcorantes Naturalesunclassified
“…A herbarium sheet was prepared and it was send to head of Botany Department of Government College , Rampurhat , Extraction may be defined as the treatment of the plant or animals tissues with solvent ,where by the medicinally active constituents are dissolve (menstrum) and most of the inert matter remains undissolved (marc) .The effective extraction of leaves depends largely on solubility and functional group consideration. [5] Soxhlet Extraction:…”
Section: Authenticationmentioning
confidence: 99%